Anthropologie de la vie et identité des objets dans le judaïsme rabbinique: sémiotique d'une aire culturelle - Vârtejanu-Joubert, Mădălina (Henoch, 2024)
Can we think of the artifact as an integral part of an anthropology of life as it has developed in the wake of the anthropology of nature founded by Philippe Descola? Judaism clearly fits within this perspective since it provides comparative research with a theory of objects in due form. The rabbis constantly circumscribe the appropriateness of various objects for the fulfilment of the commandments, revealing the way in which both "natural things" and man's transformative action and the result of that action are conceived. This article aims to support this reflection by studying two ritual objects related to the festival of Sukkot: the sekak; the roof of the sukkah hut, and the lulav, the bouquet of the four species. The making of the ritual object according to specific rules shows us its place in the encounter with the supernatural, the goal towards which any ritual device aspires.